2021
DOI: 10.1007/s00423-021-02330-6
|View full text |Cite
|
Sign up to set email alerts
|

Omitting nasogastric tube placement after gastrectomy does not enhance postoperative recovery: a propensity score matched analysis

Abstract: Background: Enhanced recovery after surgery (ERAS) program has become the main trend in gastrointestinal surgery. The aim of this study is to investigate factors in uencing the decision-making of nasogastric tube (NGT) placement and its safety and e cacy in clinical practice.Methods: We analyzed our prospectively maintained database including 287 patients underwent elective gastrectomy in our department from January 1 to December 31, 2017. All cases were divided into two groups, namely, the non-nasogastric tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Tube usage still con-tinues in the postoperative period because of the prolonged operation time and the possibility of paralytic ileus. Some studies have demonstrated that using NG/NJ tubes is not required in the postoperative period, but many surgeons have been discouraged from abandoning this practice [4,8]. Patients who did not use tubes were given an oral diet earlier in the postoperative period, and no one required NG/NJ tube de-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tube usage still con-tinues in the postoperative period because of the prolonged operation time and the possibility of paralytic ileus. Some studies have demonstrated that using NG/NJ tubes is not required in the postoperative period, but many surgeons have been discouraged from abandoning this practice [4,8]. Patients who did not use tubes were given an oral diet earlier in the postoperative period, and no one required NG/NJ tube de-…”
Section: Discussionmentioning
confidence: 99%
“…According to research, all forms of gastric resection may be performed without the needing for an NG/NJ tube [3,8,17]. In our study, regardless of the extent of gastric resection and lymphadenectomy (D1/D2), the NG/NJ tube was not used in all patients in the non-NG/NJ tube group.…”
mentioning
confidence: 82%
“…In this study in the modi ed group, four patients experienced postoperative ileus, and two patients required NGT reinsertion, but these patients recovered without surgery. Prolonged perioperative fasting and NGT are likely to induce nausea and delay bowel function recovery and the patients without a postoperative NGT recovered postoperative bowel movement earlier than patients with an NGT and that routine postoperative NGT intubation is unnecessary after elective surgery [14]. It is unclear whether early removal of NGT accelerates the recovery of bowel movement.…”
Section: Discussionmentioning
confidence: 99%
“…In this study in the modified group, four patients experienced postoperative ileus, and two patients required NGT reinsertion, but these patients recovered without surgery. Prolonged perioperative fasting and NGT are likely to induce nausea and delay bowel function recovery, and the patients without a postoperative NGT recovered postoperative bowel movement earlier than patients with an NGT and that routine postoperative NGT intubation is unnecessary after elective surgery [ 17 ]. Although previous reports suggested omitting NGT placement does not enhance the postoperative recovery in gastric cancer [ 17 ], our modified ERAS included that omitting NGT enhanced the postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged perioperative fasting and NGT are likely to induce nausea and delay bowel function recovery, and the patients without a postoperative NGT recovered postoperative bowel movement earlier than patients with an NGT and that routine postoperative NGT intubation is unnecessary after elective surgery [ 17 ]. Although previous reports suggested omitting NGT placement does not enhance the postoperative recovery in gastric cancer [ 17 ], our modified ERAS included that omitting NGT enhanced the postoperative recovery. It is speculated that this is the effect of multiple items such as early oral intake, reduction of intestinal edema due to early termination of infusion, and administration of herbal medicine: Dai-kenchu-to.…”
Section: Discussionmentioning
confidence: 99%